2019
DOI: 10.1038/s41535-019-0178-8
|View full text |Cite
|
Sign up to set email alerts
|

Isostructural Mott transition in 2D honeycomb antiferromagnet V0.9PS3

Abstract: We present the observation of an isostructural Mott insulator-metal transition in van-der-Waals honeycomb antiferromagnet V0.9PS3 through high-pressure x-ray diffraction and transport measurements. The MPX3 family of magnetic van-der-Waals materials (M denotes a first row transition metal and X either S or Se) are currently the subject of broad and intense attention, but the vanadium compounds have until this point not been studied beyond their basic properties. We observe insulating variable-range-hopping typ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
35
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(39 citation statements)
references
References 58 publications
4
35
0
Order By: Relevance
“…It facilitates the semiconductor-metal transition and leads to an enhancement of interlayer exchange interaction, the latter of which suggests the effective dimensionality of exchange interaction increases significantly. Similar increase in the effective dimensionality of transport behaviors is observed in V 0.9 PS 3 under high pressure [55]. The intriguing AFM to FM half-metallic transition could be in principle studied by refractive magnetic circular dichroism, magneto-optical Kerr effect microscopy, and transport measurement.…”
Section: Electronic Structures Under Different Pressures and Its Transupporting
confidence: 58%
See 1 more Smart Citation
“…It facilitates the semiconductor-metal transition and leads to an enhancement of interlayer exchange interaction, the latter of which suggests the effective dimensionality of exchange interaction increases significantly. Similar increase in the effective dimensionality of transport behaviors is observed in V 0.9 PS 3 under high pressure [55]. The intriguing AFM to FM half-metallic transition could be in principle studied by refractive magnetic circular dichroism, magneto-optical Kerr effect microscopy, and transport measurement.…”
Section: Electronic Structures Under Different Pressures and Its Transupporting
confidence: 58%
“…These transition behaviors are distinctly different from extensively studied FePS 3 [43], where the Mott insulator-metal transition in FePS 3 happens between B-II and B-III phases. In contrast, the transition in CoPS 3 is isostructural in T-I phase, which is similar to V 0.9 PS 3 [55]. Based on the above analysis, this continuous transition among various magnetic states in CoPS 3 , from AFM semiconductor to FM half-metal and then to FM metal during the gradual pressurization process, should bring more possibilities to its applications.…”
Section: Electronic Structures Under Different Pressures and Its Tranmentioning
confidence: 67%
“…Thus, the existence of disconnected nickel regions in samples may only affect the absolute value of resistivity, but not gives rise to the intrinsic insulating behavior. In principle, high pressure can compress the cell volume and reduce the lattice parameters of compound, resulting in insulator-metal transitions and even superconductivity [40,41] . The clear suppression of insulating behavior in our high-pressure study may be induced by the modification of the bands, or the weakening of the correlation effect, which lead to an enhanced effective density of states at the Fermi energy.…”
Section: Discussionmentioning
confidence: 99%
“…Pressure or compressive strain might also be an alternative way to tune the properties of the 2D vdW magnets without introducing disorder or impurities to the system. It has been recently shown that pressure can be effectively used to modify the magnetic, electronic, and optical properties of 2D vdW magnets both in bulk and atomically thin samples [18][19][20][21][22][23][24][25][26][27][28][29] .…”
Section: Introductionmentioning
confidence: 99%
“…However, the high-pressure behavior of CrPS 4 remains unexplored to date. By comparison, high-pressure investigations on the closely related systems such as TMP(S, Se) 3 (TM = transition metal) in which the TM ions form a layered honeycomb lattice, have revealed Mott insulator-metal and structural transitions in MnPS 3 18 , FePS 3 20,25,27 , FePSe 3 25 , and recently Mott isostructural transition in V 0.9 PS 3 26 . In this work, we examine the effects of pressure on the optical, electronic, and vibrational properties of layered CrPS 4 through the use of optical absorption, photoluminescence, resistivity, and Raman spectroscopy measurements.…”
Section: Introductionmentioning
confidence: 99%